ESCHATOLOGICAL ANALYSIS: ANGELS CAPTURED AND BOUND THE DEVIL FOR A THOUSAND YEARS, STUDY OF REVELATION 20:2 - Banarto, Kris; Kansil, Dicky Welly (Publisher: Bethel Press; Unit Penerbit: STT Bethel Indonesia Jakarta, 2025)
The Millennial Kingdom is often understood differently by believers, in general some believe that the Millennial Kingdom will happen in the future, some believe that the Millennial Kingdom does not exist, and argue that the Millennial Kingdom is already happening now. Regarding the rapture, there are also various opinions, some believe that before the seven-year period of the antichrist the church of God will be raptured so that it will not experience torture, others argue that the church will be raptured after the three and a half years of the antichrist, and another view says that the church of God will only be raptured after the end of the antichrist. These differences in views must be straightened out according to God's teachings in the Bible, with biblical hermeneutic analysis. This study aims to find out how angels capture and bind the devil for a thousand years. This research method uses literature studies, exegeses and hermeneutics of verses, and interpretations of theologians. The conclusion of this study is that the devil is bound for a thousand years as proof of the prophecy that there will be a time when the Lord Jesus will rule theocratically together with believers and so that the devil does not lead the nations astray.